ANALISIS PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PADA PABRIK KELAPA SAWIT PT. WAWASAN KEBUN NUSANTARA BENGKAYANG - Tri Diana; Amelia Amelia (Jurnal Ekonomi STIEP, 2020)
Work stress is a condition of tension that creates a physical and psychic imbalance that affects emotions, thinking processes, and the condition of an employee.Stress jobs can be interpreted as the perceived pressure of an employee because job assignments cannot be filled. The purpose of this research is to know the effect of working pressure on the performance of employees at the palm oil plant PT. WKN Bengkayang.The analytic tools used were to use multiple linear regression, classical ASUSMI tests and coefficesian significance tests. This means that stress arises when an employee is not able to meet the demands of the job. From the research results obtained the magnitude of the stress effect of the working variable (X) on the performance variable (Y) 15.9%. The significant value of the stress variable is 0.000 < 0.05 (smaller than the probability value), which means the variable stress affects the performance variable. Then the t-count for the 3.762 variable stress is greater than the t-table which is 1.992 and physical regression in the direction of positive values of 0.395. This suggests that the stress is positive and significant in performance